Legal Awareness and Community Empowerment in Enhancing Access to Justice: A Qualitative Study - Harun Pandia (LPPM Akademi Teknik Adikarya, 2025)
This study examines the role of legal awareness and community empowerment in enhancing access to justice within marginalized communities. Grounded in the perspectives of Legal Studies and Sociolegal Studies, the research explores how individuals’ understanding of legal rights and their capacity for collective action influence their ability to seek and obtain justice. The study aims to analyze the extent to which legal awareness contributes to empowerment processes and to identify structural and cultural barriers that hinder equitable access to justice. This research employs a qualitative approach using in-depth interviews, focus group discussions, and document analysis to capture the lived experiences of community members, legal aid providers, and local stakeholders. Data were analyzed through thematic analysis to identify recurring patterns related to legal knowledge, empowerment strategies, and institutional responsiveness. The findings reveal that increased legal awareness significantly enhances individuals’ confidence and willingness to engage with formal legal mechanisms. Moreover, community empowerment initiatives, such as legal education programs and grassroots advocacy, play a crucial role in bridging the gap between formal legal systems and vulnerable populations. However, the study also identifies persistent challenges, including limited institutional capacity, socio-economic inequalities, and cultural perceptions that discourage legal engagement. The research concludes that strengthening access to justice requires an integrated approach that combines legal literacy, participatory empowerment, and institutional reform. This study contributes to the development of more inclusive legal frameworks by emphasizing the importance of community-based strategies in achieving substantive justice.